The Fading of Yearnings for Liberation and Passage When the Bet on Love Is Lost: A Study of the Memoirs and Letters of an Arabian Princess - El-Fakki El-Bashir, Abdalla (Hawwa, 2020)
This paper presents a study of the memoirs and letters of Princess Sālima bt. Saʿīd (d. 1922), whose father, Saʿīd b. Sulṭān (d. 1856), was the ruler of Oman and Zanzibar from 1832 to 1856. One hundred and fifty years ago, the princess entered into a relationship with a young German man, Rudolph Ruete. After the princess fell pregnant, putting her in conflict with the stipulations of her Islamic religion, she decided to elope with her lover and to bet on him. The paper argues that the princess was a revolutionary woman in opposition to traditional Zanzibari culture, and that her story highlights clearly the issue of women and the crisis of freedom in Arab and Islamic culture during that time.
Keywords: Littérature – Zanzibar